O Grivo faz obra de atrovo: experiência estética em “Cara-de-Bronze”, de João Guimarães Rosa - VIDAL, Eduardo de Figueiredo (Universidade Federal do Pará, 2023)
“Cara-de-Bronze” is one of the seven narratives of Corpo de baile (1956), by João Guimarães Rosa (1908-1967), it contains elements that make it unique among the others, because it hybridizes the lyrical, epic and drama, presents paratexts and footnotes that enhance its poetic language and its virtual meanings. As a theoretical and methodological alternative, the investigations of Hans Robert Jauss (1921-1997) in the field of Aesthetic Experience (1979; 1986) and Literary Hermeneutics (1983) support us in the interpretive process of the work, because according to the theorist, every experience with art results from aesthetic pleasure, which is manifested through three functions: poiesis, aisthesis and katharsis, that is, the producing, receiving and communicative functions of art. In this way, the present research aims to interpret how the three functions of the aesthetic experience in "Cara-de-Bronze" occur, which are manifested in the relationship of the character Grivo, creator of the work, with the cowboys and with the farmer Cara-de-Bronze, her spectators. The hermeneutic method considers the diachronic aspect of the reception of the work, so the dialogues with critical texts about Rosa’s narrative make up the last moment of the interpretation, they will go through the classical reception — Benedito Nunes ([1967] 2009) and Dirce Riedel (1971) — the contemporary — Sofia Elaine Cerni Baú (1996), Clara Rowland (2003), Parreira Duarte (2006) and Yudith Rosenbaum (2011). With this, we seek to expand the interpretative horizon of the narrative “Cara-de-Bronze”, by João Guimarães Rosa.